Revisiting Ricardo Palma in the hundredth anniversary of his death - Forgues, Roland (2019)
This article reviews the concept of dissent in Ricardo Palma's work. We use the term "dissent" in the sense that Mario Vargas Llosa (1971) developed. Briefly, we reveal here how the dissent in Palma is masked by an apparent social and cultural conformism destined to subtly question the structures of colonial and patriarchal power and its survival in the Peruvian republic.